Sosialisasi dan Lomba Kreativitas Daur Ulang Sampah di SMP Advent Tompaso Kabupaten Minahasa, Sulawesi Utara - Deviana Munthe; Sudarno P Tampubolon (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Abstract The concept of waste reduction (reduce), recycling or reusing (reuse/recycle), and safe disposal (dispose) is highly crucial in mitigating waste pollution today. The Community Service activity carried out at SMP Advent Tompaso through socialization and a creative waste recycling competition themed